2016
DOI: 10.1007/s00705-016-2918-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a nanoparticle-assisted RT-PCR assay to distinguish field strains and attenuated strains of porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea virus (PEDV) can cause serious disease and even death in neonatal piglets, resulting in serious damage to the swine industry worldwide. Open reading frame 3 (ORF3) is the only accessory gene in the PEDV genome. Previous studies have indicated that PEDV vaccine strains have a partial deletion in ORF3. In this study, a nanoparticle-assisted polymerase chain reaction (nanoparticle-assisted RT-PCR) assay targeting the ORF3 of PEDV was developed to distinguish PEDV field strains from atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Although several standard detection methods, for example virus isolation, virus neutralization tests, and indirect immunofluorescence assay, are available for the detection of viruses, these techniques are time‐consuming and not suitable for detecting large‐scale samples. Currently, polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA) methods for the detection of these viruses have been reported (Luo et al, ; Ma et al, ; Zhu, Wang, Cui, & Cui, ). Due to the high pathogenicity of these viruses to suckling piglets, which have immature immune systems and few antibodies, ELISA is inefficient for detecting these viruses compared to PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Although several standard detection methods, for example virus isolation, virus neutralization tests, and indirect immunofluorescence assay, are available for the detection of viruses, these techniques are time‐consuming and not suitable for detecting large‐scale samples. Currently, polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA) methods for the detection of these viruses have been reported (Luo et al, ; Ma et al, ; Zhu, Wang, Cui, & Cui, ). Due to the high pathogenicity of these viruses to suckling piglets, which have immature immune systems and few antibodies, ELISA is inefficient for detecting these viruses compared to PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Since an attenuated live vaccine (CV777) was used for immunizations before the PEDV outbreak, we investigated whether PEDV was caused by a wild strain or a vaccine strain. The CV777 vaccine strain was characterized by a 49-bp deletion in the ORF3 gene, which is usually used in the differential diagnosis between wild and vaccine strains ( Zhu et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…When obvious cytopathic effects were apparent, including the characteristic fused-syncytium cell formation, the viral supernatant was collected and used for RNA extraction for subsequent cloning and sequencing. The 49-bp deletion of the ORF3 gene was assessed for the differential diagnosis between vaccine and field strains for PEDV positive samples ( Zhu et al. 2016 ; He et al.…”
Section: Methodsmentioning
confidence: 99%
“…There is a short period of carrying attenuated vaccine virus in the orally immunized pig population, and the possibility that the wild-type strains and the attenuated vaccine strains will exist simultaneously in the pig herds [12,13]. In recent study, multiple strains were also found in many immunized pig population in China [4,14,15], and phylogenetic analysis of the whole genome also showed that there are multiple variation sites in PEDV genome [16,17]. The antigenicity of vaccines derived from classical vaccine strains may be altered due to these genetic mutations, resulting in low vaccination e ciency and inability to protect pigs from variant PEDV strains [16].…”
Section: Discussionmentioning
confidence: 99%